Rebuilding women's livelihoods strategies at the city fringe: Agency, spatial practices, and access to transportation from Semmencherry, Chennai. (July 2016) - Alberts, Anna; Pfeffer, Karin; Baud, Isa
Abstract: Existing debates suggest that resettlement leads to exclusion of the urban poor from the city, linked to interrupted livelihoods and lack of accessibility to the city. This paper analyses the ways in which public transport mobility plays a role in the livelihood strategies of women living in a resettlement area at the fringe of Chennai, India. The main question addressed is how women exercise agency in embedding spatial practices within their livelihood strategies to reconnect to the city. The analysis is based on 4 months fieldwork in Semmencherry Resettlement Area in Chennai (India). It combines a qualitative analysis with a spatial exploration drawing on concepts from debates on the livelihoods approach, spatial practices, and accessibility and transport-related exclusion. Results show that the more agency women have to negotiate livelihoods strategies, the better they can take complex decisions on accessing resources over large distances and minimizing their adverse effects. We argue that combining a livelihood with a spatial analysis is important because it shows how spatial exclusion has to be assessed according to women's own priorities and decisions concerning spatial practices as part of livelihoods strategies. Accessibility and recreating relational spaces may both widen women's opportunities as well as overstretch their physical and financial resources. Highlights: Mapping spatial practices produces new insights into women's livelihood strategies. Links to city are maintained by half the household. Women make deliberate decisions around daily activities after resettlement. Spatial exclusion is related to household composition and gendered responsibilities. Extended households offer women more chances to access work and other resources.